Preparation and characterization of steam and CO2 activated carbon from Brazil nut shell - Pryscila Machado de Castro; Stela Regina Ferrarini; Michelle da Silva Ferreira Rimoli; Aloir Antônio Merlo; Roberta Martins Nogueira; Evaldo Martins Pires (Bioscience Journal, 2023)
Activated carbon is a porous material with several industrial applications. In this research, brazil nut shell was used to produce activated carbon, a promising raw material based on its low cost and high quality. Also, nut processing generates an extensive amount of waste, requiring proper disposal. The carbon was produced at temperatures of 600, 700, and 800 °C and activated by physical method using steam or CO2. Yield was calculated, and the activated carbon was analyzed according to the following physical-chemical parameters: water content, volatile material, fixed carbon, ash, apparent density, and pH. Infrared spectroscopy and BET adsorption isotherms were also performed. The fixed carbon contents of the carbons produced at 700 and 800 °C remained above 84%. The pH values characterized them as basic. The surface areas of the carbon obtained at 800 °C were 397 ± 8 m2 g–1 and 325 ± 7 m2 g–1 in those which were activated by steam and CO2, respectively.